An Augmented Reality-Based Interactive Learning Application for Teaching Food Chains in Elementary Schools - Qorimah, Esti Nur; Sutama, Sutama; Hidayati, Yulia Maftuhah (Profesi Pendidikan Dasar, 2024)
Augmented Reality (AR) media is considered important due to its ability to engage elementary school students. The purpose of this study was to develop an AR-based application for teaching food chains in elementary schools. This research followed the Research and Development (R&D) model proposed by Borg & Gall. Data were collected through assessment sheets completed by expert validators, and data analysis involved both quantitative and qualitative methods. The results showed that: 1) the media received a feasibility score of 4.71; 2) the material received a score of 4.11; 3) practitioners rated the media highly, with a score of 4.83; and 4) in the limited trial, 8 out of 10 students scored above the Minimum Mastery Criteria in quizzes. Therefore, it can be concluded that the AR-based food chain application is highly feasible for use in elementary schools. Through AR, students can observe in real time how plants, herbivores, carnivores, and decomposers interact within an ecosystem